The History of Protectionism and Free Trade in the World: How Does it Impact Indonesia? - Larasati, Dorothea Bening (UI Scholars Hub, 2025)
International trade plays an important role in Indonesia's economy, with protectionism and free trade being the two main approaches in the country's trade policy. Protectionism, which aims to protect domestic industries by restricting imports, is often challenged in the face of the need to integrate global markets. In contrast, free trade seeks to open markets without barriers, which can accelerate economic growth and improve international relations. This research aims to explore the impact of protectionism and free trade policies on the Indonesian economy and provide recommendations for the government. The research uses a qualitative approach through a literature study that involves analyzing economic theories, Indonesian export-import data, as well as policies implemented by the government. The results show that while protectionism provides protection for domestic products, it can limit innovation and reduce the competitiveness of Indonesian industries in the global market. On the other hand, free trade opens up wider market opportunities, but can affect local industries, especially MSMEs, which find it difficult to compete with imported products. In conclusion, it is important for Indonesia to balance these two policies by optimizing support for the domestic sector and strengthening international trade policies. The recommendation for the government is to strengthen policies that support the competitiveness of local industries without hindering global market integration.